Assessment and simulation of a solid waste dumpsite impact on the surrounding water resources: A case study in Abu Zaabal, Egypt - Mohamed E. El-Mathana (Elsevier, 2021)
Indiscriminate dumping of solid wastes and the resulting groundwater contamination is a major issue, especially for developing countries. The main objective of this paper is to develop a groundwater mass transport model in order to study the effect of an open solid waste dumpsite on the water quality of water resources within the region around it. The harmful effects of indiscriminate solid wastes disposal by open dumping, which is still followed in many developing countries around the world, is highlighted. Abu Zaabal dumpsite; which is located in Qalyubiyah Governorate, Egypt; receives huge amounts of wastes daily causing leachate generation that percolates deep into the soil and polluting the shallow aquifer. The Groundwater Modeling System (GMS) software was used to model the groundwater flow and mass transport, using data collected from the site investigation and literature historical data available. Of the several contaminants measured in the site, six critical contaminants; namely Total Dissolved Solids (TDS), Lead, Boron, Nitrate, Manganese and Chemical Oxygen Demand (COD); were chosen to be modeled. The developed model was used to simulate the six contaminants using a transient-state model and concentration values for two different scenarios. Scenario-1 assumes that the dumpsite will be active until 2080, whereas Scenario-2 represents imminent closure of the dumpsite. The model results of each contaminant were calculated over 100-year interval, from 1980 until 2080, and the results of 2080 were presented. The results showed that the dumpsite had a major impact on the nearby water bodies, Abu Zaabal ponds and Belbais Drain. Moreover, the closure of the dumpsite showed that the maximum concentration of the majority of the considered contaminants was decreased by approximately 60–65%.